The Evaluation of Biochemical Parameters of Ethanolic Extract of Lepidium meyenii in Male Wistar Rats : Evaluation of Biochemical Parameters of Ethanolic Extract of Lepidium meyenii - Hamdalat Folake Muritala; Habeebat Oyewesi; Tobiloba ogunlana; Loveth Ajakaiye; Kehinde Aina; Waleed Ibrahim; Fiyinfoluwa Patricia Ogunyinka; Halimat Aliyu; Clement Olatunbosun Bewaji (Journal of Tropical Life Science, 2022)
The effects of ethanolic extract of Lepidium meyenii on some biochemical parameters were investigated. Forty male Wistar rats were grouped into five groups of eight animals each. Group 1 served as the control and received distilled water throughout the period of administration while groups 2, 3, 4 and 5 received 25, 50, 75 and 100 mg/kg body weight of ethanolic extract of L. meyenii respectively for seven and fourteen days. After seven days of administration, four animals from each of the groups were sacrificed and the rest were sacrificed after fourteen days, and biochemical alterations were monitored. The effects after the seven-day administration revealed that there was no significant (p > 0.05) difference in organ-body weight percentage, liver functional indices, kidney functional indices and the activity of some cytosolic and membrane bound enzymes studied butÂ following the fourteen-day administration, significant difference (p < 0.05) were observed with increase in organ-body weight percentage of selected organs, increase in serum activity of the enzymes: ALT, AST, ALP; and aberrant variation in the kidney functional indices studied at the 50, 75 and 100 mg/kg body weight showing selective toxicity of the extract. Inconclusive results were obtained in the analysis of the seminal parameters for both the seven- and fourteen-day administration while similar effects on hematological parameters were observed for both the seven- and fourteen-day administration. This study showed that the extract may be hepatotoxic and nephrotoxic when administered beyond seven days in male Wistar rats especially at 100 mg/kg body weight.